Lipid quality deteroriation of bagridae catfish (Mystus nemurus) during storage. - Widjaja, Willy Pranata; Abdulamir, Ahmed Sahib; Abu Bakar, Fatimah; Saari, Nazamid; Ishak, Zamri; Abdul Hamid, Azizah (Medwell Publishing, 2009)
Lipid damage indices of whole freshwater catfish (Mystus nemurus) stored at ambient (28±2°C), chilled (10±2°C) and iced (2±1°C) temperature for 24 h, 10 and 20 days, respectively, were studied. Lipid quality deterioration was evaluated by measuring free fatty acids, peroxide values, p-anisidine value, thiobarbituric acid and polyene index. The results showed that Mystus nemurus is a fatty fish species with 16.8-19% of fat content. The lipid hydrolysis and lipid oxidation that occurred after 12 h at ambient, 8 days at chilled and 16 days at iced storage increased significantly (p<0.05) to unacceptable levels with decreased polyene. This study demonstrates evidence-based research that typical storage conditions for Mystus nemurus is of practical significance to producers and consumers.